Analysis Of Corrosion Rate For Steel Concrete Reinforcing Pda Reinforced Concrete In Sea Water Media - Helmy Alian (Universitas Sriwijaya, 2017)
Â There is so many buildings that built in corrosive environment, which is because lack of terrain or the functions of the buildings themselves. Many of the buildings use steel as reinforcement to strengthen the construction. The strength of buildings will Decrease if the reinforcing steel is corroded because the steel is very easily corroded. This research is to analyze kind of corrosion, corrosion rate of the steel frame in sea water or salty water. Plain reinforcing steel is used in this research with three different brands as specimens to compare the corrosion rate in sea water medium. Observation results show that the kind of corrosion that occurs in three different kinds of the steel is uniform corrosion. Calculation of corrosion rate in this research shows weight loss method. Calculation result of corrosion rate show that A steel brand has the highest endurance Compared to B and C brand. Difference of corrosion rate is because of chemical composition, Also in each kind of steel is added many elements such as chrome, manganese, copper and nickel to increase of corrosion endurance. Difference of elements that added in steel is Affect the corrosion endurance. Base on the research result can be concluded that corrosion endurance in every brand of stainless still in excellent category because the value of corrosion rate is between 0.02 to 0.01 mm / yr